MAKNA GERAK TARI TOR-TOR DALAM PERKAWINAN BATAK TOBA DI DESA SILALAHI, KECAMATAN SILAHISABUNGAN, KABUPATEN DAIRI, PROVINSI SUMATERA UTARA - Selti Astria Mandalahi; Ferdinand Kerebungu; Veronike E.T. Salem (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
When the Toba Batak ethnic wedding party in the Silalahi area, where Tortor was held, was no longer a medium of communication by paying attention to the meaning of every symbol of the movements that exist in Tortor, but Tortor was held to only be an art that could entertain and enliven the party and some had purposes can seek profit for the party organizers. This study aims to determine the meaning contained in the Tortor dance in Batak Toba marriage in Silalahi Village and to find out how the community's understanding of the meaning contained in the Tortor dance movement in Batak Toba marriage in Silalahi Village. The study used qualitative methods with the informant as the data source, and the researchers themselves as a means of capturing data using interview guidelines. The results of the research on the meaning of the Tortor dance movement in Toba Batak marriage show that the meaning of Manea-nea in a Toba Batak marriage is a way of welcoming the bride and groom and their entourage to enter the building. Mamasu-masuya where the bride and groom ask for blessings from parents, parhata kings and invited guests. Manombaya is the last worship performed by the bride and groom to their parents.